The Effect of Consumption On The Society Welfare In Sampang District - Arifin, Syamsul; Anisa, Nur Aini; Siswohadi, Siswohadi; Megasari, Aisyah Darti; Darim, Abu (Yayasan Ahmar Cendekia Indonesia, 2020)
Welfare is one of the most important aspects of maintaining and fostering social and economic stability because it is necessary to minimize social jealousy in society. This study aims to analyze the effect of economic consumption on the welfare of the society in Sampang district. This research uses quantitative approach. This research conducted in Sampang District by using time series data and this research is analyzed by using linear regression technique. According to the result of research indicate that consumption has significant positive effect on the welfare of the society in Sampang district. Based on the results of research that has been conducted, consumption significantly influences the welfare of the society in Sampang district.